Remarkable response to dacomitinib in a patient with leptomeningeal carcinomatosis due to EGFR‐mutant non‐small cell lung cancer - Shun Mizusaki; Kohei Otsubo; Toshifumi Ninomiya; Hidenobu Arimura; Yuko Tsuchiya‐Kawano; Koji Inoue (Thoracic Cancer, 2021)
Dacomitinib, a second‐generation epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitor, is a standard therapeutic option for patients with EGFR‐mutant non‐small cell lung cancer (NSCLC). However, its efficacy in patients with central nervous system lesions is unclear. Here, we describe a case of EGFR‐mutant NSCLC whose neurological symptoms were due to leptomeningeal carcinomatosis that was successfully treated with dacomitinib. After initiation of dacomitinib, the neurological symptoms of the patient were remarkably improved and leptomeningeal dissemination and brain metastases were shown to have regressed on magnetic resonance imaging (MRI) scan. To our knowledge, this is the first report showing the efficacy of dacomitinib in a patient with leptomeningeal carcinomatosis due to EGFR‐mutant NSCLC. The current case suggests that dacomitinib is a novel treatment option for patients with EGFR‐mutant NSCLC accompanied by central nervous system lesions, even those with symptomatic leptomeningeal carcinomatosis. Key points Significant findings of the study This is the first report showing the efficacy of dacomitinib in a patient with leptomeningeal carcinomatosis due to EGFR‐mutant NSCLC. What this study adds The current case suggests that dacomitinib is a novel treatment option for patients with EGFR‐mutant NSCLC accompanied by CNS lesions, even in those with symptomatic leptomeningeal carcinomatosis.